Establishment of contamination-free culture and In vitro regeneration of shorea leprosula miq. - Liu, Yan Tin (unimas, 2009)
Shorea leprosula Miq., a fast growing dipterocarps, has potential for reforestation of degraded forest. However, planting stock of this species is scarce because fruiting is irregular and the seeds are recalcitrant. Micropropagation has been considered as an alternative to mass produce the planting stock. The objective of this study was to develop an effective surface sterilization protocol to establish contamination-free culture as the first step towards development of micropropagation of S. leprosula. The surface sterilization protocol developed so far started with soaking the fieldderived shoot-tip and nodal explants in a fungicide solution for one and three hours respectively. The explants were then dipped in 75% ethanol for one minute and surface sterilized in 5% Clorox added with Tween 20 for 10 minutes and Chlorine Dioxide at 50 ppm for 10 minutes. The explants were then rinsed with autoclaved-RO water for at least three times. Nodal explants were pulse-treated with 10 ml/L PPM for overnight whereas shoot-tip explants were pulsedtreated with PPM at 5 ml/L for an hour. Surface-sterilized explants were trimmed and cultured on MS basal medium supplemented with 20 g/L sucrose. BAP and TDZ were found to be effective in inducing new buds growth on nodal explants. Nodal explants inoculated on MS basal medium supplemented with 2 mg/L BAP and 0.1 mg/L NAA showed new buds growth.